Change in the party system from liberal to ethnic-based polarisation - Nacevska, Elena (Teorija in praksa, 2019)
Although party systems (PSs) have been studied a lot, there is still insufficient research into the transition from a PS characterised by the predominance of liberal-based political parties into a PS in which ethnic or religious-based parties dominate. The article helps rectify this deficiency by combining a quantitative approach using numerical measurements of PSs and a qualitative approach for determining the characteristics of PSs and how they change. This combination of approaches in the empirical study of the PS and the way it developed in Macedonia between 1990 and 2018 proved crucial for revealing the growing polarisation within the PS based on the stronger ethnic polarisation, an aspect uncapturable by the usual quantitative measurement of PS change.
Keywords: Ethnic relations; Etnični odnosi; Party systems; Polarizacija; Polarization; Political parties; Politične stranke; Strankarski sistemi